(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study analyzes the impact of Non-tariff Measures (NTMs) on the direction of Agricultural and Processed Food exports (APFE) after the establishment of WTO. The countries have been classified into three groups viz Developed, Developing and LDC countries, to assess the impact of NTMs on the direction of export. An increasing trend was observed for the agricultural and processed food export to Developed Countries for selective years in terms of export value. But in terms of percentage share, a decreasing trend has been observed. There is no difference has been seen in the percentage share and value of agriculture trade to developing countries. It has been recognized that there is an increasing trend presented for LDC for all the selective years compared to the base period in value terms and it has also been noted that the percentage share of APF export to LDC has been increasing during the period. To analyze the impact of Non-Tariff Measures (NTMs) on the Direction of India’s exports, particularly in agriculture and food products, the prevalence of NTMs in trade is calculated by the way of incidence indicators viz. the coverage Ratio (CR), the Frequency Index (FI), and the Prevalence Score (PS). The data for all the indicators have been collected from the UNCTAD-TRAINS database for all the sectors and the agricultural sector. The countries those rank declined in 2022 compared to the year 1995 in terms of the import value of agricultural and processed food from India, these countries have the highest level of coverage ratio, frequency index, and prevalence score. It is confirmed that the nexus between NTMs and India’s agricultural and processed food exports in the case of India after establishment of WTO.